The dot - Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2003)
Vashti believes that she cannot draw, but her art teacher's encouragement leads her to change her mind.
Keywords: Self-confidence -- Juvenile fiction; Art -- Juvenile fiction; Schools -- Juvenile fiction; Self-confidence -- Fiction; Art -- Fiction; Schools -- Fiction; Juvenile materials